The Role of Foreign Intervention in the Doctrinal Wars in France - Ammar Mohammed Ali Al-Ta’ey, Meriam Hadi Alyasseri, (Opción, 2019)
The aim of the study is to investigate the role of foreign intervention in the doctrinal wars in France from 1579 to 1588 via comparative qualitative research methods. As a result, the king did not want the Guise’s to return to the royal court, so he tried to push away Henri de Guise especially when the interest between them has ended. In conclusion, Guise was looking forward to being in this place as a reward for defeating the Germans and the Swiss so he decided to request for privileges as compensation for the wages of war.